A multi-criteria decision framework for circular wastewater systems in emerging megacities of the Global South - (:unkn) unknown (Elsevier BV, 2024)
Lima faces increasing water stress due to demographic growth, climate change and outdated water management infrastructure. Moreover, its highly centralized wastewater management system is currently unable to recover water or other resources. Hence, the p...
Keywords: Aguas residuales; Ciudades emergentes